Using MARRVEL v1.2 for Bioinformatics Analysis of Human Genes and Variant Pathogenicity. Issue 1 (19th July 2019) - Wang, Julia; Mao, Dongxue; Fazal, Fatima; Kim, Seon‐Young; Yamamoto, Shinya; Bellen, Hugo; Liu, Zhandong
Abstract: One of the greatest challenges in the bioinformatic analysis of human sequencing data is identifying which variants are pathogenic. Numerous databases and tools have been generated to address this difficulty. However, these many useful data and tools are broadly dispersed, requiring users to search for their variants of interest through human genetic databases, variant function prediction tools, and model organism databases. To solve this problem, we collected data and observed workflows of human geneticists, clinicians, and model organism researchers to carefully select and display valuable information that facilitates the evaluation of whether a variant is likely to be pathogenic. This program, Model organism Aggregated Resources for Rare Variant ExpLoration (MARRVEL) v1.2, allows users to collect relevant data from 27 public sources for further efficient bioinformatic analysis of the pathogenicity of human variants. © 2019 by John Wiley & Sons, Inc.